Hubungan antara aktiviti fizikal dan indeks jisim badan murid lelaki luar bandar - Bakhtiar Afindi, Mohd Khushairy; Abd Razak, Mohd Radzani; Ismail, Erwan (Secholian Publication, 2022)
Physical activities and fitness should be prioritized in order to guarantee healthy body and obtain as well as maintain the ideal Body Mass Index (BMI). This research aimed at studying the relationship between physical activities and BMI of secondary school male students in rural areas. The research population are 390 Form 5 male students in Tampin district which were selected using stratified random sampling method. 180 research sample were then selected through Krecjie and Morgan sample size determination table (1970). This survey-based research utilises a questionnaire modified from Global Physical Activity Questionnaire (GPAQ) by World Health Organisation (WHO). This research shows that male students in Tampin district are not active in physical activities despite having normal BMI readings. As a result, they tend to have low health risk.